Effective tools to learn lean thinking and gather together academic and practice communities - Alves, Anabela Carvalho (2018)
Lean Engineering learning should be compulsory on engineering curricula, and, particularly, on the Industrial Engineering field. Prior to the integration on the Industrial Engineering curriculum, Lean Engineering was already implemented by many organizations and, often, fostered by consulting companies. For this reason, if engineering students were taught about Lean Engineering, they would be better prepared to assume a leadership role in their organizations and/or to better communicate with Lean consultants. Based on a literature review and on the authors' practice, this paper discuss some approaches that have been used for Lean Engineering learning. Some learning experiences implemented in an engineering master's degree are presented which make use of effective educational tools based on active methodologies, such as hands-on simulation, Problem or Project-Based Learning (PBL), Conceive-Design-Implement and Operate (CDIO) initiative, among others. This paper also presents these tools and how they address Lean Engineering learning through the lens of Lean Thinking principles. Their advantages in Lean Engineering learning are discussed by gathering the academic and practitioners' communities opinions. These are based on final year projects' reports, feedback from students and from organization supervisors.